Featured properties of Li+-based battery anode: Li4Ti5O12. Issue 24 (7th April 2020) - Nguyen, Thi Dieu Hien; Pham, Hai Duong; Lin, Shih-Yang; Lin, Ming-Fa
Abstract : A theoretical framework based on first-principles calculations is developed for the essential properties of the 3D ternary compound Li4 Ti5 O12, a Li + -based battery anode. Abstract : 3D ternary Li4 Ti5 O12, a Li + -based battery anode, presents an unusual lattice symmetry (triclinic crystal), band structure, charge density, and density of states under first-principles calculations. It is a large direct-gap semiconductor with E dg ∼ 2.98 eV. The atom-dominated valence and conduction bands, the spatial charge distribution and the atom- and orbital-decomposed van Hove singularities are available for delicate identifications of multi-orbital hybridizations in Li–O and Ti–O bonds. The extremely non-uniform chemical environment, which induces very complicated hopping integrals, directly arises from the large bonding fluctuations and the highly anisotropic configurations. Also, the developed theoretical framework is very useful for fully understanding cathodes and electrolytes of oxide compounds.